CONDITION ASSESMENT OF GLENDENG BRIDGE USING BRIDGE MANAJEMENT SYSTEM (BMS) IN TUBAN DISTRICT - Ahmad Faathir Wicaksono; Ratna Handayani (Journal Innovation of Civil Engineering (JICE), 2020)
The valuation of Glendeng Bridge condition in Tuban District is needed to evaluate the deterioration of the bridge caused by the Bengawan Solo river flooding since the high rainfall which was made worst by the excavation of the bridge protection structure. This research is conducted through the direct visual survey by recorded the detail element of the bridge deterioration based on the deterioration code and assessed the level of severity and structural condition whether the element affecting the other element and suffering the overall bridge condition. This valuation of the bridge is based on the Bridge Management System (BMS) which was being studied by the Pusjatan Ministry of Public Work in 2012. The research shows that the main element deteriorated was the approach embankment, retaining wall, rubber bearing and earthquake dump isolator on the north side of Tuban caused by the drainage on the surface, excavation of the front of approach road and the flooding of Bengawan Solo river. The overall condition of the bridge is valuated with 4 (four) mark so that the bridge is needed to have the strengthening and replacement on the deteriorate elements